Penegakan Hukum Keimigrasian Terhadap Pelanggaran Kebijakan Bebas Visa Dan Second Home Visa Bagi WNA - Zalza Meira Cahyani; Faizatun Nadhifah; Lia Riska Mala; Achmad Fathoni Alfahmi (Fakultas Syariah UIN Antasari, 2023)
Violations of the visa-free policy can occur in the form of overstays, unauthorized activities, and visa abuse. Meanwhile, second home visa violations can be classified into three categories, namely duration of stay violations, activity violations, and visa extension violations. This research highlights the need for new arrangements in supervision procedures for foreigners holding free visit visas and second home visas. Currently, immigration still faces challenges in carrying out effective supervision related to the implementation of visa-free and second-home visa policies. Therefore, this study is intended to conduct an analysis related to violations of visa-free and second-home visa policies as well as immigration supervision of Foreign Nationals (WNA). This research uses normative juridical methods, without ruling out philosophical and sociological elements. Which in this study results in the conclusion that immigration law enforcement against violations of visa-free policies and second home visas for foreigners is an important step to safeguard the interests of the country and protect the integrity of the immigration system. Through effective and fair law enforcement, it is expected to create an immigration environment that is orderly, safe, and in accordance with applicable regulations, both for the state and interested foreigners.